Impact of exercise on older adults' mood is moderated by sleep and mediated by altered brain connectivity. Issue 11 (17th November 2020) - Alfini, Alfonso J; Won, Junyeon; Weiss, Lauren R; Nyhuis, Casandra C; Shackman, Alexander J; Spira, Adam P; Smith, J Carson
Abstract: Older adults comprise the fastest growing global demographic and are at increased risk of poor mental health outcomes. Although aerobic exercise and sleep are critical to the preservation of emotional well-being, few studies have examined their combined mood-enhancing effects, or the potential neural mechanisms underlying these effects. Here, we used a randomized crossover design to test the impact of acute exercise on mood and the intrinsic functional connectivity (iFC) of the cingulo-opercular network in physically healthy older adults. Wrist actigraphy provided objective indices of sleep. Results revealed that 30 min of moderate-intensity aerobic exercise acutely enhanced positive affect (PA) and reduced iFC between the cingulo-opercular network and the hippocampus. Both effects were magnified among older adults with greater sleep disturbance. Exercise-induced changes in hippocampal iFC mediated relations between sleep disturbance and exercise-induced increases in PA. These findings provide evidence that aerobic exercise enhances mood, that it does so by altering connectivity between the anterior insula—a key hub in the cingulo-opercular network—and the hippocampus and that lower sleep quality is a stronger predictor of these effects among older adults. These observations underscore the benefits of moderate-intensity exercise—a safe and scalable behavioral intervention—and provide new clues about the neural circuitry underlying the interactive effects of sleep and exercise on mood.